Menenun Persekutuan yang Kudus: Kajian Teologi Feminis - Kolimon, Mery; Ataupah, Felpina Norma (Asosiasi Teolog Indonesia, 2025)
Protestant churches in Indonesia, including in West Timor, still find it difficult to articulate the relationship between living believers and their deceased family members and ancestors. This article aims to develop a contextual theology of holy communion in West Timor. The article draws upon a dialogue between the practice of offering woven cloths to bereaved families among the Timaubus community in Kupang Regency, East Nusa Tenggara, with the Christian observance of holy communion (communio sanctorum). In the Timaubus tradition, when a close relative dies, women present woven cloths, which serve not only as a sign of solidarity and support for the bereaved family (amut) but also as provisions for the deceased and a deposit for the ancestors (sofit). At burial, a woven cloth from the closest relative is placed in the coffin as a gift to the ancestors. This article suggests that Christians in Timor offer woven cloths to bereaved families and their deceased, as an expression of their faith in relation to holy communion. Our study employs qualitative methods, including in-depth interviews, observations, focus group discussions, and literature review. We utilize Elizabeth Johnson’s feminist theology to create a dialogue between the practice of presenting woven cloths at death and feminist theological principles concerning communio sanctorum.